Anticoagulant-active sulfated arabinogalactan from Chaetomorpha linum: Structural characterization and action on coagulation factors. (15th August 2020) - Qin, Ling; He, Meijia; Yang, Yajing; Fu, Zitao; Tang, Cuicui; Shao, Zhuling; Zhang, Junyan; Mao, Wenjun
Highlights: A polysaccharide from the green alga Chaetomorpha linum is isolated and characterized. The polysaccharide is a sulfated arabinogalactan with arabinofuranose units. The polysaccharide possesses high anticoagulant activity in vitro and in vivo . The polysaccharide exerts strong inhibition effects on the coagulation factors XII, XI, IX and VIII. The polysaccharide is a thrombin inhibitor mediated by antithrombin III or heparin cofactor II. Abstract: A sulfated polysaccharide from the green alga Chaetomorpha linum, designated CLS4, was isolated by water extraction, anion-exchange and size-exclusion chromatography. Chemical and spectroscopic analyses demonstrated that CLS4 was a sulfated arabinogalactan, which was constituted by (1→6)-β-d -galactopyranose and (1→5)-α-l -arabinofuranose residues with sulfate groups at C-2/ C-3 of (1→5)-α-l -arabinofuranose and C-2/C-4 of (1→6)-β-d -galactopyranose. CLS4 possessed strong anticoagulant activity in vitro or in vivo as evaluated by activated partial thromboplastin time and thrombin time assays. CLS4 largely inhibited the activities of the coagulation factors XII, XI, IX and VIII. CLS4 was a potent thrombin inhibitor mediated by antithrombin III (ATIII) or heparin cofactor II, and it also effectively stimulated the factor Xa inhibition by potentiating ATIII. Moreover, CLS4 had a high thrombolytic activity in vitro as assessed by clot lytic rate assay. The results suggested that CLS4 could be a promising source of anticoagulant agent.